Winged Fruits of Deviacer in the Oligocene from the Ningming Basin in Guangxi, South China - Chen, Yunfa (PLoS One, 2015)
Deviacer guangxiensis Chen & Manchester sp. nov. is described based on asymmetric samaras from the Oligocene Ningming Formation in Guangxi, South China, representing the first documentation of Deviacer fossils in Asia. The Oligocene species, with relatively large fruits, represents the youngest record of the genus so far known; all other records are from the Paleocene and Eocene, or late Eocene—early Oligocene in western North America and Europe. It indicates that the extinct genus, Deviacer, was widely distributed in the northern hemisphere during the Paleogene.